Pembelajaran Selama Krisis COVID-19: Meta-Analisis dari Sudut Hasil Belajar yang Diukur - Maximus Tamur; Emilianus Jehadus; Habibi R. P. Negara; Muhammad Daut Siagian; Marzuki Marzuki; Rini Sulastri (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: A new civilization in the world of education caused by the COVID-19 pandemic crisis has triggered the reformulation of learning activities. The consensus regarding this reformulation has resulted in a transition to a virtual-based learning process (PBV). Correspondingly, throughout 2020 there have been numerous individual studies on the effects of PBV with inconsistent findings. A meta-analysis study was conducted to analyze related findings, and consider the results for future PBV implementation. Research samples in the form of individual studies were collected from the ERIC, SAGE, and Google Scholar databases. This study considers learning outcomes as a moderating variable. The estimation method uses a random-effect model, and the calculation tool is the Comprehensive Meta-Analysis (CMA) software. The results of the analysis revealed that overall PBV had a moderate impact on student learning outcomes (ES = 0.67; standard error 0.15). The results of the moderator analysis revealed that the implementation of PBV was more effective in low-level cognitive domains. The implications of the research results are discussed to provide important information as a fundamental idea for further PBV research and development.